The Influence of Service Quality, Facilities, and Promotion on Customer Satisfaction and Implications on Repurchase Intention of Expedition Services - Utama, Adi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Customer satisfaction will be built if the company improves service quality, this will enable customers to make repurchase intentions. This study aims to determine the influence of service quality, facilities and promotion on customer satisfaction and implications on repurchase intention. The research method used is descriptive quantitative. The sample was determined using a saturated sampling technique with 100 respondents. The results of the study indicate that partially service quality, facilities and promotion have an impact on customer satisfaction, service quality, Promotion and customer satisfaction partially influence repurchase intention.